Arterial ischemic stroke in HIV: Defining and classifying etiology for research studies. Issue 4 (August 2016) - Benjamin, Laura A.; Bryer, Alan; Lucas, Sebastian; Stanley, Alan; Allain, Theresa J.; Joekes, Elizabeth; Emsley, Hedley; Turnbull, Ian; Downey, Colin; Toh, Cheng-Hock; Brown, Kevin; Brown, David; et al.
Abstract : HIV infection, and potentially its treatment, increases the risk of an arterial ischemic stroke. Multiple etiologies and lack of clear case definitions inhibit progress in this field. Several etiologies, many treatable, are relevant to HIV-related stroke. To fully understand the mechanisms and the terminology used, a robust classification algorithm to help ascribe the various etiologies is needed. This consensus paper considers the strengths and limitations of current case definitions in the context of HIV infection. The case definitions for the major etiologies in HIV-related strokes were refined (e.g., varicella zoster vasculopathy and antiphospholipid syndrome) and in some instances new case definitions were described (e.g., HIV-associated vasculopathy). These case definitions provided a framework for an algorithm to help assign a final diagnosis, and help classify the subtypes of HIV etiology in ischemic stroke.